Membrane technology and environmental applications - Zhang, Tian C. (American Society of Civil Engineers, 2012)
Sponsored by the Membrane Technology Task Committee of the Environmental Council of the Environmental and Water Resources Institute of ASCE. Membrane Technology and Environmental Applications explains the use of membrane materials as a direct, effective, and sustainable way to address environmental problems. Membranes are a core technology for separating material mixtures, such as wastewater and saltwater, and offer significant advantages over other technologies. Membrane technologies are relatively simple in concept and operation, flexible, and compatible with integrated systems in many environments. They can also minimize the use of treatment chemicals, the production of residuals, and energy consumption. This volume provides in-depth technical information on the fundamentals, applications, and recent advances of membrane technology, including state-of-the-art reviews of current research, critical analysis of new processes and materials, and avenues for further study. Chapters examine environmental applications such as treatment of drinking water, wastewater, and industrial wastewater; water reclamation and reuse; desalination; removal of arsenic and emerging contaminants; treatment of greywater and rainwater, and the production of bioproducts from wastewater sludge. New research is described on such topics as membrane fouling, process enhancement, membrane biofilm reactors, nanomaterials, and new separation techniques. Chapters contain extensive illustrations, case studies, summary tables, and up-to-date references. For practicing engineers, environmental and treatment-plant managers, and government officials, this volume is an essential guide for designing and implementing membrane technologies. Educators, graduate and undergraduate students, and researchers involved in environmental engineering and science will find this book to be a valuable learning tool and reference.
Keywords: Membrane separation.; Water -- Purification -- Membrane filtration.; Gas separation membranes.; elektronické knihy; electronic books